2013
DOI: 10.1007/s11274-013-1585-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of amylolytic, xylanolytic, and cellulolytic microorganisms extracted from the gut of the termite Reticulitermes santonensis by means of a micro-aerobic atmosphere

Abstract: The aim of this work was to isolate enzyme-producing microorganisms from the tract of the termite Reticulitermes santonensis. The microorganisms were extracted from the guts and anaerobic (CO₂ or CO₂/H₂) and micro-aerobic atmospheres were used to stimulate growth. Three different strategies were tried out. First, the sample was spread on Petri dishes containing solid media with carboxymethylcellulose, microcrystalline cellulose or cellobiose. This technique allowed us to isolate two bacteria: Streptomyces sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The culture-based approach used here led us to obtain strains restricted to the readily cultivable ones, and so key components of the samples and enrichment cultures might have been missed in our work. Other culture-dependent studies utilizing similar enrichment procedures reported the dominance of Firmicutes and a comparable taxonomic distribution for soil samples [36], guts of xylophagous insects [10,30], and compost [37]. Among the most frequent genera obtained, Bacillus spp.…”
Section: Discussionmentioning
confidence: 59%
“…The culture-based approach used here led us to obtain strains restricted to the readily cultivable ones, and so key components of the samples and enrichment cultures might have been missed in our work. Other culture-dependent studies utilizing similar enrichment procedures reported the dominance of Firmicutes and a comparable taxonomic distribution for soil samples [36], guts of xylophagous insects [10,30], and compost [37]. Among the most frequent genera obtained, Bacillus spp.…”
Section: Discussionmentioning
confidence: 59%
“…Members of Pseudomona sp. were reported as cellulolytic (Huang et al, 2012; Pourramezan et al, 2012; Nandimath et al, 2016) and β-glucosidase activity was also reported (Tarayre et al, 2014). …”
Section: Discussionmentioning
confidence: 98%
“…Higher-termites are able to recycle 65–99% of the ingested cellulose and hemicelluloses respectively, whereas some scarabs can degrade up to 65% of the fibers present in their diet ( Cazemier et al, 1997 ; Ohkuma, 2003 ). Since few decades, efforts are focused on the understanding of lignocellulose degradation in insect digestive tracts in order to use this knowledge to improve biomass conversion efficiency in bioreactors ( Brune, 1998 ; Huang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%